Development Of AnIot-Based Healthcare System (International Journal of Environmental Sciences, 2025)
In order to provide medical aid from a distance, telemedicine is a multidisciplinary concept that includes physiology, biomedical apparatus, and telecommunications. Numerous barriers to receiving health care support, including a lack of doctors, a huge population, and geographic distance, can be effectively addressed by telemedicine. Notwithstanding the many benefits, telemedicine is not being used to its full potential because the necessary equipment is now somewhat costly. The need for telemedicine is growing as the population grows and healthcare facilities are dispersed inefficiently. Conventional methods of monitoring and disseminating physiological data are time-consuming because they are not automated and require skilled personnel to manage. The effective deployment of telemedicine applications requires IoT-based systems with physiological monitoring capabilities. For telemedicine to be effective, many sensors must be linked into IoT-based systems in order to track patient data and transmit it to distant medical experts.